In-programme leadership development for psychiatric higher trainees: The Royal College of Psychiatrists' Leadership and Management Fellow Scheme. Issue 3 (11th August 2021) - Bagepalli-Krishnan, Deepa; Gibson, Russell; Goyal, Satnam; Ko, Ba Min (Adam); Till, Alex; Crimlisk, Helen
Abstract : Introduction: The Royal College of Psychiatrists' (RCPsych) Leadership and Management Fellow Scheme was established to develop and support a new cohort of medical leaders within psychiatry. Sponsored and mentored by a trainee's local education provider, the scheme combines a high-impact national leadership and management training programme, with a novel in-programme apprenticeship model, where Fellows gain local leadership experience. Method: An internal review team conducted a mixed-methods evaluation of feedback from Fellows and Mentors on the scheme's structure, delivery, provision of individual leadership development and the impact fellows had on their teams and the organisations within which they were embedded. Results: With a response rate of 67% (n=20) from Fellows and 30% (n=7) from Mentors, a clear benefit from the scheme was observed, alongside opportunities for improvement. Strengths of the scheme included the bespoke in-programme design, mentoring from a senior medical leader, networking opportunities, and experiential learning through local leadership experience, which additionally promoted medical engagement within organisations. Opportunities for improvement included strengthening existing offers, particularly mentoring relationships and enhancing the network established between fellows. Conclusions: A bespoke, uniprofessional and in-programme leadership and management fellow scheme can play an important role in the development of future medical leaders within psychiatry.